Up to this pointe - Longo, Jennifer (Random House, 2016)
Devastated when her dream of becoming a professional ballerina falls through, seventeen-year-old Harper Scott takes a job as a research assistant, wintering over at McMurdo, a U.S. science station at the tip of Antarctica where, for the first time, she considers other possible futures.